Progress in Computing, Analytics and Networking Proceedings of ICCAN 2019 - Das, Himansu; Pattnaik, Prasant Kumar; Rautaray, Siddharth Swarup; Li, Kuan-Ching (Advances in Intelligent Systems and Computing, 2020)
XXVI, 669 p. 332 illus., 207 illus. in color.